2019
DOI: 10.1007/s00280-018-03765-3
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib dose allocation study of oral administration of lucitanib given in combination with fulvestrant in patients with estrogen receptor-positive and FGFR1-amplified or non-amplified metastatic breast cancer

Abstract: Purpose The primary objective of this multicentric dose allocation and dose expansion study was to determine the MTD and the DLTs of the lucitanib (a tyrosine kinase inhibitor of the FGFR/VEGFR/PDFGR pathways)/fulvestrant combination. Methods Postmenopausal women with ER+/HER2− mBC, who have relapsed during or after treatment with fulvestrant, were eligible. The study had a dose allocation part to assess the tolerability of the combination followed by a dose expansion part. Results Eighteen patients with ER+, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
9
1
Order By: Relevance
“…Preclinical studies in cell lines and xenografts have demonstrated more effective inhibition of tumor cell growth with combined blockade of FGFR1 and ER using both lucitanib and fulvestrant (28). The efficacy of lucitanib in combination with fulvestrant in a small study showing CBR of 55.6% in patients with metastatic HR þ / HER2 À breast cancer with unselected FGFR1 status appeared to be numerically higher than monotherapy lucitanib in our study (48). Given the role of FGFR1 aberrations in the development of endocrine resistance, it may be useful to explore the combination of lucitanib and fulvestrant as a potential treatment for HR þ /HER2 À FGFR1-amplified breast cancers after resistance to first-line endocrine therapy.…”
Section: Discussioncontrasting
confidence: 39%
“…Preclinical studies in cell lines and xenografts have demonstrated more effective inhibition of tumor cell growth with combined blockade of FGFR1 and ER using both lucitanib and fulvestrant (28). The efficacy of lucitanib in combination with fulvestrant in a small study showing CBR of 55.6% in patients with metastatic HR þ / HER2 À breast cancer with unselected FGFR1 status appeared to be numerically higher than monotherapy lucitanib in our study (48). Given the role of FGFR1 aberrations in the development of endocrine resistance, it may be useful to explore the combination of lucitanib and fulvestrant as a potential treatment for HR þ /HER2 À FGFR1-amplified breast cancers after resistance to first-line endocrine therapy.…”
Section: Discussioncontrasting
confidence: 39%
“…Single-agent FGFR1-inhibitors do not show sufficiently high activity in advanced HR+ breast cancer to warrant further development [24,29,30]. Combinations of a hormonal agent and an FGFR1inhibitor show variable activity [26,27]. Our results advance in the task of finding a therapeutic scenario and a patient sub-population where FGFR inhibitors would deserve clinical investigation: HR+ breast cancer patients with amplification and/or overexpression of FGFR1 upon progression to aromatase inhibitors.…”
Section: Discussionmentioning
confidence: 87%
“…Selective FGFR inhibitors (1)(2)(3)(4) have shown activity in tumors with FGFRs mutations, amplifications, or fusions [19,[22][23][24][25]. The role of FGFR inhibitors in breast cancer, however, is yet unclear [26][27][28][29]. Preclinical and clinical data suggest limited single-agent efficacy [24,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients in the MONALEESA-2 study, FGFR1 amplification detected in ctDNA was associated with a shorter PFS under ribociclib [56]. Initial studies failed to demonstrate a significant activity of the FGFR1-3 inhibitors lucitanib [57] and dovitinib [58] in combination with fulvestrant in endocrine-resistant patients. Clinical development is now focusing on novel FGFR inhibitors, such as erdafitinib, which is currently being investigated in combination with palbociclib and fulvestrant in CDK4/6i-pretreated patients (Table 1).…”
Section: Investigational Cdk4/6i Combinations After Cdk4/6i Progressionmentioning
confidence: 99%